Proceedings of the 2009 ACM Symposium on Applied Computing 2009
DOI: 10.1145/1529282.1529350
|View full text |Cite
|
Sign up to set email alerts
|

Fast networking with socket-outsourcing in hosted virtual machine environments

Abstract: This paper proposes a novel method of achieving fast networking in hosted virtual machine (VM) environments. This method, called socket-outsourcing, replaces the socket layer in a guest operating system (OS) with the socket layer of the host OS. Socket-outsourcing increases network performance by eliminating duplicate message copying in both the host OS and the guest OS. Furthermore, socket-outsourcing significantly enhances inter-VM communication within the same host OS since it enables network packets to byp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…To eliminate redundant processing, socketoutsourcing [21] and VMM-bypass network [22] is invested the guest application which has the awareness [23] of the virtualization. Nevertheless, they only succeeded in improving the performance up to about 60% of the native device, since their notifications of completion were still engaged by the hypervisor.…”
Section: Related Workmentioning
confidence: 99%
“…To eliminate redundant processing, socketoutsourcing [21] and VMM-bypass network [22] is invested the guest application which has the awareness [23] of the virtualization. Nevertheless, they only succeeded in improving the performance up to about 60% of the native device, since their notifications of completion were still engaged by the hypervisor.…”
Section: Related Workmentioning
confidence: 99%
“…To support these design objectives, the following three core capabilities should be provided: (i) determining whether the receiver VM is co-resident with the sender VM on the same host, (ii) support both local and remote inter-VM communication protocols and upon detection of local mode of communication, automatically switching to the shared memory based channel, and (iii) the shared memory based inter-VM communication should be incorporated into the existing virtualized platform in an efficient and fully transparent manner [4][5][6][7][8]10].…”
Section: B Functionality and Design Objectivesmentioning
confidence: 99%
“…This is because the abstraction of VMs supported by VMM technology does not differentiate whether the data request is coming from co-resident VMs or not. Several research projects [2][3][4][5][6][7][8][9][10][11] have demonstrated that. Linux guest domain shows lower network performance than native Linux [12], when an application running on a VM communicates with another VM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socket-Outsourcing (Eiraku, 2009), XenSockets (Zhang, 2007) Xway (Kim, 2008) and XenLoop (Wang & Wright, 2008) are using this approach.…”
Section: Introductionmentioning
confidence: 99%